Persuasion social influence and compliance gaining - Gass, Robert H.; Seiter, John S. (New York Routledge, 2022)
The Seventh Edition of this field-leading textbook provides an accessible and rigorous presentation of major theories of persuasion and their applications to a variety of real-world contexts. In addition to presenting established theories and models, this text encourages students to develop and apply general conclusions about persuasion in real-world settings. Along the way, students are introduced to the practice of social influence in an array of contexts (e.g., advertising, marketing, politics, interpersonal relationships, social media, groups) and across a variety of topics (e.g., credibility, personality, deception, motivational appeals, visual persuasion). The new edition features expanded treatment of digital and social media, up-to-date research on theory and practice, an increased number of international cases, and new and expanded discussions of topics such as disinformation and 'fake news,' youth social activism, nationalism and patriotism, and the neuroscience of deception. This is the ideal textbook for courses on persuasion in communication, psychology, advertising, and marketing programs. Instructors can also use the book's downloadable test bank, instructor's manual, and PowerPoint slides in preparing course material"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Persuasion (Psychology).; Influence (Psychology).; Manipulative behavior